Laden choirs : the fiction of Patrick White - Wolfe, Peter, 1933- (University Press of Kentucky, 1983)
In 1973 the Australian novelist Patrick White won the Nobel Prize for Literature, the year that his great novel of family ties and change, The Eye of the Storm, was published and became a bestseller in America and Europe. Yet White is still not widely known or read, and few writers of today have provoked so many contradictory judgments. Now Peter Wolfe has written the first book-length study of the work of this brilliant and haunting novelist. The study offers a subtle, penetrating examination of White's style, his skill in building narrative tension, and also the depth and complexity reflecte.